TASK-BASED LANGUAGE TEACHING (TBLT) APPROACH: IMPLICATIONS ON READING COMPREHENSION - Fachruddin, Achmad Taqlidul Chair (ETERNAL (English, Teaching, Learning, and Research Journal), 2020)
Task-based language teaching (TBLT) has exceedingly been written in many research reports but research examining the impacts of TBLT on student’s reading comprehension remains limited. Recent studies indicate that TBLT is promoting real communication or the exchange of meanings rather than forms. The reading intention is to excerpt meaning from text by developing the literal, inferential and extrapolative comprehension of readers, and this depends upon both decoding and language comprehension skills. Recently there has been growing interest in developing students’ ability to read comprehensibly in a classroom situation. One way to develop students’ reading ability is by committing Task-Based Language Teaching in teaching reading. This article explores the impacts of TBLT on three levels of students’ reading comprehension, literal, inferential and extrapolative comprehension. This research employed the quasi-experimental method involving fifth-semester students of Sekolah Tinggi Ilmu Kesehatan Panakukang Makassar. The instruments were reading tests and questionnaires. The data from reading tests were used to figure out the effect of TBLT on students’ reading comprehension (literal, inferential, and extrapolative comprehension) by using a t-test while the data from questionnaires were to figure out the students’ motivation. The findings revealed that TBLT has an impact on students reading comprehension. Sequentially, the most evolving level of comprehension was inferential, extrapolative, literal comprehension. Moreover, the result of a questionnaire displayed that the students who were taught through TBLT became more motivated to read in the domain of reading efficacy, reading curiosity, and reading challenge motivation